The concept of law - Hart, H. L. A (Clarendon law series., 1994)
"H. L. A. Hart's The Concept of Law is without question the most important work of legal philosophy written this century; no other study has made such an important contribution to the study of jurisprudence and legal philosophy. Since it was first published in 1961 its elegant language and balanced arguments have inspired generations of students to address the wider problems associated with the study of law." "In this long awaited new edition Hart presents a postscript in which he re-examines the foundations of his philosophy of law, with special attention to Professor Dworkin's criticism of it. With dispassionate lucidity he shows how much of the criticism stems from misunderstanding and confusion of thought. The postscript provides a clarification and a restatement of the fundamental tenets of his position." "This thought-provoking new edition will re-open a wide range of debates and will be welcomed by all those with an interest in legal philosophy and jurisprudence."--BOOK JACKET.